Nasal Continuous Positive Airway Pressure vs. Nasal Intermittent Positive Pressure Ventilation as Initial Treatment After Birth in Extremely Preterm Infants - Kostekci, Yasemin Ezgi; Okulu, Emel; Bakirarar, Batuhan; Kraja, Elvis; Erdeve, Omer; Atasay, Begum; Arsan, Saadet (Frontiers in Pediatrics, 2022)
Objective: Noninvasive respiratory support strategies are known to reduce the complications of invasive mechanical ventilation in preterm infants. Nasal continuous positive airway pressure (NCPAP) and nasal intermittent positive pressure ventilation (NIPPV) are commonly used ones. The recent meta-analyses indicated that early NIPPV did appear to be superior to NCPAP for decreasing respiratory failure and need for intubation among preterm infants with respiratory distress syndrome (RDS). The aim of the study was to compare the short-term outcomes of extremely preterm infants who received NCPAP or NIPPV as an initial treatment of RDS. Methods: This retrospective study included infants born before 29 weeks’ gestation between January 1, 2018 and December 31, 2021 who received noninvasive respiratory support with NCPAP or NIPPV. For every infant included in the cohort, only the first episode of NCPAP or NIPPV as initial treatment was evaluated. The primary outcome was need for intubation within 72 h, and the secondary outcomes were need for intubation within 7 days, administration of surfactant, prematurity related morbidities, mortality, and death or bronchopulmonary dysplasia (BPD). Results: During the study period, there were 116 inborn admissions of preterm infants born <29 weeks’ gestation and 60 of them met the inclusion criteria. Of these 31 (52%) infants received NCPAP while 29 (48%) infants received NIPPV at first hours after birth. There were no differences in baseline demographics between the groups (p>0.05). Blood gas parameters (pH, pCO2, HCO3 and lactate) at admission were not different. The need for intubation within 72 h as primary outcome was similar between NCPAP and NIPPV group (35.5% vs. 34.5%, p=0.935). The rates of surfactant requirement, need for intubation within 7 days, prematurity related morbidities, mortality and death/BPD were similar among the groups (p>0.05). Conclusions: NIPPV is non inferior to NCPAP as an initial treatment in extremely preterm infants with RDS. Although the rate of intubation in first week, mortality and BPD did not differed between groups, additional studies are needed and the synchronization of NIPPV should be evaluated.